2015
DOI: 10.3390/ijerph121215038
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Interventions to Reduce Tobacco Smoke Pollution in Homes: A Systematic Review and Meta-Analysis

Abstract: Introduction: Smoke-free homes can help protect children from tobacco smoke exposure (TSE). The objective of this study was to conduct a meta-analysis to quantify effects of interventions on changes in tobacco smoke pollution in the home, as measured by air nicotine and particulate matter (PM). Methods: We searched MEDLINE, PubMed, Web of Science, PsycINFO, and Embase. We included controlled trials of interventions which aimed to help parents protect children from tobacco smoke exposure. Two reviewers identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
76
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(82 citation statements)
references
References 74 publications
1
76
1
4
Order By: Relevance
“…Interventions that have been implemented to reduce household ETS or IAP include a combination of counselling, the installation of clean chimneys, and improved ventilation in the homes of smokers. A systematic review and meta-analysis of the effectiveness of interventions to reduce ETS in homes as assessed by reduction in nicotine and PM levels found that although some benefits were documented, at follow-up, exposure was still present [114]. ETS exposure, as measured by cotinine levels, was consistently higher in children who lived in multiunit or attached housing compared to children living in detached homes, even if there were no smokers within the home [115].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interventions that have been implemented to reduce household ETS or IAP include a combination of counselling, the installation of clean chimneys, and improved ventilation in the homes of smokers. A systematic review and meta-analysis of the effectiveness of interventions to reduce ETS in homes as assessed by reduction in nicotine and PM levels found that although some benefits were documented, at follow-up, exposure was still present [114]. ETS exposure, as measured by cotinine levels, was consistently higher in children who lived in multiunit or attached housing compared to children living in detached homes, even if there were no smokers within the home [115].…”
Section: Resultsmentioning
confidence: 99%
“…ETS exposure, as measured by cotinine levels, was consistently higher in children who lived in multiunit or attached housing compared to children living in detached homes, even if there were no smokers within the home [115]. Regulations to enforce smoke-free multiunit housing is a feasible intervention, particularly for new developments [114,116] that should be considered in LMIC regions, especially where government-subsidized housing may be provided. However, in LMIC, these interventions might not always be possible.…”
Section: Resultsmentioning
confidence: 99%
“…28 Thus, it is necessary to combine effective actions to protect children at home, such as the following: I) encouraging parents to quit smoking; II) making interventions aimed at promoting smokefree households; III) implementing regulatory approaches, such as smoke-free households; IV) running public health education campaigns to encourage smoke-free households beyond the extent of regulatory approaches. 28 That said, there is not sufficient data to recommend one strategy over another to reduce ETS exposure in children or evidence of success in different contexts (healthy children, sick children, the community). 29 Impact assessments are required accordingly for each context and region so as to establish which interventions are most costeffective.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are few interventions that are effective in reducing SHS in deprived households with children 5 . Fine particulate matter (PM 2.5 ) is a significant component of indoor air pollution, and has been widely used in tobacco control research as a marker for the presence of SHS 6 .…”
Section: Introductionmentioning
confidence: 99%